The chiasm: Transfusion practice versus patient blood management - Spahn, D.; Shander, A.; Hofmann, Axel (Elsevier, 2013)
In recent years it became increasingly clear that allogeneic redblood cell (RBC) transfusions result in increased mortality andmajor adverse clinical outcomes. The major risk factors for RBCtransfusions are preoperative anaemia, high perioperative bloodloss and liberal transfusion triggers. Patient blood management(PBM), the bundle of preoperative anaemia treatment, measures toreduce perioperative blood loss and optimising anaemia tolerance,aims at minimising RBC transfusion needs and improving clinicaloutcomes. PBM has been adopted by the World Health Organizationas the new standard of care and all member states are urgedto implement this concept. Australia is leading the world in thatPBM is indeed implemented at the current time.